CHARACTERIZATION OF GASTRIC CANCER ASSOCIATED VIRULENCE FACTOR CAGPAI OF HELICOBACTER PYLORI: AN IN-SILICO STUDY - MUCCEE, F; RAZZAQ, F; AYUBE, N; IQBAL, R; RAFIQUE, F (Biological and Clinical Sciences Research Journal, 2023)
Gastric cancer (GC) is reported to be the sixth most prevalent cancer all over the world. Helicobacter pylori is one of its causative agents. Its virulence factor cytotoxin-associated gene pathogenicity island (cagPAI) induces GC via causing gastritis, DNA breakage, inhibiting p53 gene, and stimulating pathogenicity pathways. Present study has targeted this pathogenic factor. Sequences of cag1, cag2, cag5, cag6 and cag8 isoforms were retrieved from Uniprot database and subjected to in-silico tools for characterization. Tools included CELLU, Protparam, AlphaFold database, MEME suite, and STRING tool. Analysis revealed all the cag isoforms to be extracellular. All were diverse for molecular weight, isoelectric point (pI), aliphatic index, instability index, and GRAVY. Most of the conserved motifs and the interacting proteins were common among most of the proteins. Deviation in three-dimensional (3D) configuration was also recorded. This study might help design drugs against H. pylori pathogenicity factors and inhibiting cagPAI genes' interactions with other proteins. Thus, might help in reducing GC incidence.